The Nexus between The Islamic Human Development Index (I-HDI), Unemployment, and Population Growth in Influencing Poverty - Putri, Wafa Maharani; Santosa, Purbayu Budi; Zusak, M Bastomi Fahri; Mi'raj, Denizar Abdurrahman (Economica: Jurnal Ekonomi Islam, 2025)
This research investigates the relationship between the Islamic Human Development Index (I-HDI), Unemployment, Population Growth, and their impact on Poverty in G20 countries from 2010 to 2021. A purposive sampling method was used to select eight countries: the United States, Indonesia, the United Kingdom, Italy, Germany, Canada, France, and Turkey. The I-HDI was calculated using five Maqasid Shariah indicators. Unemployment was measured by the national unemployment rate, and Population Growth was represented by the annual population growth rate. A total of 384 panel data points were analyzed using the Fixed Effect Model (FEM) regression technique. The findings reveal a robust negative relationship between I-HDI and the Poverty Rate, indicating that improvements in human development are key drivers in alleviating poverty. In contrast, Unemployment shows a significant positive association with the Poverty Rate, meaning that an increase in unemployment leads to a rise in poverty levels. However, Population Growth does not exhibit a significant effect on the Poverty Rate, suggesting that demographic changes alone are not adequate to explain fluctuations in poverty across the G20 countries. These results offer valuable insights for policymakers focused on enhancing human development and addressing unemployment to effectively combat poverty.